2023
DOI: 10.1007/s12144-023-04295-9
|View full text |Cite
|
Sign up to set email alerts
|

Choosing to live environmentally childfree: private-sphere environmentalism, environmental activism, or both?

Abstract: Choosing not to have children can be considered a pro-environmental behaviour with a very high environmental impact. However, such impact calculations have been criticised for focusing only on private, individual actions. In the current article, the aim was to build on studies that have identified activist aspects of living environmentally childfree, and analyse whether this choice, in a Norwegian context, should be categorised as private-sphere environmentalism or environmental activism. This is explored thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Schneider-Mayerson (2021) suggested that reproductive behaviors have entered the ways in which people think of themselves and act as environmental actors, highlighting the intimate intersection between private action and movement participation. Similarly, asking whether living environmentally childfree is related to private-sphere environmentalism or activism, Nakkerud (2023) suggested that “eco-reproductive” concerns are both individual and collective forms of environmentalism, as they are also mobilized “to influence structures beyond one's own immediate impact” (Nakkerud 2023, p. 7). We ground our research in a similar attempt to analyze how “eco-reproductive” concerns are used as socio-political tools to appeal to decision-makers.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…Schneider-Mayerson (2021) suggested that reproductive behaviors have entered the ways in which people think of themselves and act as environmental actors, highlighting the intimate intersection between private action and movement participation. Similarly, asking whether living environmentally childfree is related to private-sphere environmentalism or activism, Nakkerud (2023) suggested that “eco-reproductive” concerns are both individual and collective forms of environmentalism, as they are also mobilized “to influence structures beyond one's own immediate impact” (Nakkerud 2023, p. 7). We ground our research in a similar attempt to analyze how “eco-reproductive” concerns are used as socio-political tools to appeal to decision-makers.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%